A roadmap to good practice for training supervisors and leadership: a European perspective - Lacey, Seán; Haven, Tamarinde; Santos, Rita; Farrelly, Tom; Murray, Máiréad; Kavouras, Panagiotis (Frontiers in Research Metrics and Analytics, 2025)
PurposeSupervision and leadership are regarded to have a major role in promoting responsible research. Various approaches to training for supervisors and leaders have been proposed. However, little is known about what works best, what kind of hurdles are faced in implementation and engagement, and what methods of assessing the effectiveness of training programs are available. Through exploring these points, this research aims to propose a roadmap to good practice for training supervisors and leadership.DesignA virtual marketplace for exchanging current practices and approaches for training supervisors and leadership took place in March 2024. Twenty-two policy makers from thirteen European countries, supervisors and senior research leaders were selected to participate, using opportunistic and purposive sampling. Facilitated using the Gather platform, the marketplace commenced with a non-European keynote speaker on training supervisors and leadership. Three main questions were brought forward for discussion separately—What works well for successful implementation? What are the challenges? How do we assess effectiveness? After the keynote presentation, marketplace participants rotated in groups between three market stalls to share thoughts on good practices for training supervisors and leadership framed around the three questions. Moderators for each of the stalls recorded detailed field notes to inform the study findings.FindingsDuring the exchange, mandatory training, especially when tailored to specific disciplines and conducted in small groups using a problem-based learning approach, was deemed effective. Awareness of power imbalances between early career researchers, supervisors, and leaders were to the fore. Critical challenges included a need for senior supervisors and leaders to participate and support research training. Also a need for systemic processes, tailored to specific local settings to avoid ad hoc implementation of policies, procedures and training. In assessing effectiveness there was an emphasis to share more research data and to utilize incidents of breaches of research integrity. The latter to be leveraged for learning purposes and transparency around the investigative process.OriginalityThere are multiple facets to good practice for training supervisors and leadership, along with a multitude of practices, however there is little evidence of practices that work, challenges around implementation, and assessing effectiveness.